2005
DOI: 10.1038/sj.npp.1300735
|View full text |Cite
|
Sign up to set email alerts
|

Administration of SCH 23390 into the Medial Prefrontal Cortex Blocks the Expression of MDMA-Induced Behavioral Sensitization in Rats: An Effect Mediated by 5-HT2C Receptor Stimulation and not by D1 Receptor Blockade

Abstract: Akin to what has been reported for cocaine, systemic administration of the dopamine D1 receptor antagonist, SCH 23390 ((R)-( þ )-7-chloro-8-hydroxy-3-methyl-1-phenyl-2,3,4,5-tetrahydro-1H-3-benzazepine hydrochloride), blocks the expression but not the induction of 3,4-methylenedioxymethamphetamine (MDMA)-induced behavioral sensitization. Since the medial prefrontal cortex (mPFC) appears to regulate the expression of sensitization to cocaine, this study examined whether microinjection of SCH 23390 into the mPFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 64 publications
2
56
1
Order By: Relevance
“…Thus, alterations in accumbal DA and/or glutamate levels consequent to stimulation of mPFC 5-HT 2C R may be one mechanism by which the 5-HT 2C R modulates the neurochemical and behavioral effects of psychostimulants. Intra-mPFC infusion of 5-HT 2C R agonists have been shown to block the hypermotive and discriminative stimulus effects of cocaine (Filip and Cunningham, 2003), and block the expression of sensitization (the progressive enhancement of the hypermotive effects of a drug following repeated drug exposure) to 3,4-methylenedioxymethamphetamine (MDMA; Ramos et al, 2005). Intra-mPFC infusion of a 5-HT 2C R antagonist, on the other hand, enhanced cocaine-induced hyperactivity and increased recognition of the stimulus effects of cocaine (Filip and Cunningham, 2003) in the absence of overt effects of intra-mPFC 5-HT 2C R ligands alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, alterations in accumbal DA and/or glutamate levels consequent to stimulation of mPFC 5-HT 2C R may be one mechanism by which the 5-HT 2C R modulates the neurochemical and behavioral effects of psychostimulants. Intra-mPFC infusion of 5-HT 2C R agonists have been shown to block the hypermotive and discriminative stimulus effects of cocaine (Filip and Cunningham, 2003), and block the expression of sensitization (the progressive enhancement of the hypermotive effects of a drug following repeated drug exposure) to 3,4-methylenedioxymethamphetamine (MDMA; Ramos et al, 2005). Intra-mPFC infusion of a 5-HT 2C R antagonist, on the other hand, enhanced cocaine-induced hyperactivity and increased recognition of the stimulus effects of cocaine (Filip and Cunningham, 2003) in the absence of overt effects of intra-mPFC 5-HT 2C R ligands alone.…”
Section: Discussionmentioning
confidence: 99%
“…The PFC is densely innervated by serotonin (5-HT) neurons of the midbrain (Van Bockstaele et al, 1993) and actions via the family of 5-HT 2 receptors (5-HT 2 R) provides an important modulatory influence over PFC function (Pompeiano et al, 1994;Clemett et al, 2000;Lopez-Gimenez et al, 2001). Recent reports have outlined an inhibitory role for the PFC 5-HT 2C R in mediating the behavioral effects of psychostimulants such as cocaine (Filip and Cunningham, 2003) and 3,4-methylenedioxymethamphetamine (MDMA; Ramos et al, 2005). While both transcript and protein for the 5-HT 2C R have been localized in PFC (Pompeiano et al, 1994;Clemett et al, 2000;Lopez-Gimenez et al, 2001;Pandey et al, 2006), a better understanding of the mechanisms of action through which the PFC 5-HT 2C R controls stimulant-induced behaviors is required, and a first step in this analysis is to gain a more complete understanding of the localization of the 5-HT 2C R protein in PFC.…”
mentioning
confidence: 99%
“…5 A, B,D). Ramos et al (2005) showed that administration of SCH23390 into the medial prefrontal cortex (mPFC) prevents the expression of 3,4-methylenedioxymethamphetamine-induced behavioral sensitization through the blockade of serotonin 5-HT 2C , but not D 1 -like receptors. To exclude a role for the 5-HT 2C receptor in the development of cocaine-induced impairment of DHPG-LTD, we administered the specific 5-HT 2C receptor antagonist RS102221 (2 mg/kg) before the daily injection of cocaine.…”
Section: Cocaine Withdrawal Impairs Dhpg-ltd Via the Activation Of D mentioning
confidence: 99%
“…Several groups of investigators have demonstrated that the repeated administration of MDMA also results in long-term neuroadaptations in the mesolimbic DA pathway that are manifested as an enhancement of the locomotor stimulating effect of MDMA, i.e., behavioral sensitization (Kalivas et al, 1997;McCreary et al, 1999;Ramos et al, 2005). Kalivas et al (1997) also have shown that the repeated administration of MDMA results in cross-behavioral sensitization to the locomotor stimulating effect of cocaine.…”
Section: Long Term Effects Of Repeated Mdma Administrationmentioning
confidence: 99%